WIPDash: Work Item and People Dashboard for Software Development Teams - Jakobsen, Mikkel R.; Fernandez, Roland; Czerwinski, Mary; Inkpen, Kori; Kulyk, Olga; Robertson, George (12th IFIP TC13 Conference in Human-Computer Interaction (INTERACT 2009), 2009)
We present WIPDash, a visualization for software development teams designed to increase group awareness of work items and code base activity. WIPDash was iteratively designed by working with two development teams, using interviews, observations, and focus groups, as well as sketches of the prototype. Based on those observations and feedback, we prototyped WIPDash and deployed it with two software teams for a one week field study. We summarize the lessons learned, and include suggestions for a future version.